Pelvic Congestion Disease with Amplatzer Vascular Plug Embolization: A Case Report - Hamisi, Andy A.; Tjandra, Djony E.; Khosama, Yuansun (Syifa'Medika, 2026)
Pelvic congestion disease is a prevalent condition causing chronic pelvic pain in women, primarily due to venous insufficiency in the pelvic region. Endovascular embolization, particularly using the Amplatzer Vascular Plug (AVP), has emerged as an effective therapeutic option for treating PCD. This case report presents a 34-year-old female with chronic left lower abdominal pain, diagnosed with PCD and successfully treated with AVP embolization. Preoperative diagnostic imaging, including multislice computed tomography (MSCT) and venography, identified left ovarian vein reflux. Following embolization, the patient showed significant symptom relief, with no recurrence during follow-up. Literature indicates that embolization, particularly with AVP, offers superior occlusion and fewer complications compared to traditional coil embolization. The procedure is minimally invasive, with low complication rates, and offers durable long-term results. Despite the effectiveness, there is a need for improved standardization in treatment protocols and classification systems to optimize PCD management. The SVP classification system provides a useful framework, but a more management-oriented approach is necessary for tailored treatment planning.